A study of prescription auditing in inpatient general medicine in tertiary care government hospital - Kumar, Yogi Eshwar P.; Rajasekhar, Giri D. (International Journal of Research in Medical Sciences, 2020)
Background: Irrational prescribing is a global problem. Prescription auditing can help to find the medication errors caused by the Inappropriate prescribing. It is the systematic tool for analysing the quality of medical care, including the procedures used for diagnosis and treatment. Methods: An observational, non-interventional study carried in general medicine department. A list of 10 questions were prepared to assess the appropriateness of prescribing patterns. Results: A total of 110 prescriptions were collected and audited. Out of 110 prescriptions 6 (5%) prescriptions have therapeutic duplications and 21 (19%) classes of drugs in the prescription have interactions with each other. Found 8 (7%) drug food interactions. Found 100% appropriateness of drug ordered based on patient diagnosis, dosage of drug, frequency of drug, route of administration, drug intended to have a drug order in the medication chart, medication orders are clear, legible, dated, timed, names and signed, medication chart do not have any unapproved abbreviations Conclusion: This study shows most of the prescribers need to check for drug duplication, drug-drug interactions and drug-food interactions before prescribing the medicines.